The Effect Of Perception Of Organizational Support, Work Life Balance And Employee Retention On Turnover Intention At CV Jodion Unggul Perkasa In Prambanan, Sleman Regency - Devia Putri Veronika Sari; Subiyanto, Didik; Ahyar Syafwan Lysander, Mohammad (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of perceived organizational support, work–life balance, and employee retention on turnover intention among employees of CV Jodion Unggul Perkasa in Prambanan, Sleman Regency. A quantitative method was employed using survey data collected from 50 employees through purposive sampling. Data were analyzed using multiple linear regression with SPSS. The results indicate that perceived organizational support, work–life balance, and employee retention have positive and significant effects on turnover intention, both partially and simultaneously. The findings imply that organizations need to implement balanced human resource strategies to improve employee retention while minimizing turnover intention. Keywords: Perceived Organizational Support, Work–Life Balance, Employee Retention, Turnover Intention, Human Resource Management, SMEs, Employee Behavior, Organizational Support.